Development of reversed-phase high performance liquid chromatography methods for quantification of two isomeric flavones and the application of the methods to pharmacokinetic studies in rats (2015)
Isomers 5,7-dihydroxy-3,6,8-trimethoxy-2-phenyl-4H-chromen-4-one (5,7–dihydroxy-3,6,8 trimethoxy flavone) (flavone A) and 3,5-dihydroxy-6,7,8-trimethoxy-2-phenyl-4H-chromen-4-one (3,5-dihydroxy-6,7,8-trimethoxy flavone) (flavone B) have recently demonstrated differential antineoplastic activities against pancreatic cancer in vitro. These studies also indicated that these compounds target highly tumorigenic cells while sparing normal cells. The in vivo antitumor activities of these flavones have not been determined, and detection protocols for these compounds are needed to conduct pre-clinical assays following intravenous dosing. Here, we report methods developed using acetonitrile to extract two flavone isomers and corresponding internal standards, celecoxib and diclofenac, from rat plasma. Separation was achieved using a Shimadzu liquid chromatography system with a C18 column and mobile phase acetonitrile/water (60:40 and 70:30 for flavones A and B, respectively) containing 0.2% acetic acid and 0.05% triethylamine at a flow rate of 0.4 mL/min and detection at 245 nm. Calibration curves ranging from 250 to 2500 ng/mL and 2500 to 100,000 ng/mL for both flavones were linear (r2 ≥ 0.99) with the lower limits of quantification being 250 ng/mL. Recovery of concentrations 250, 1000, 2500, 5000, and 100,000 ng/mL ranged from 87 to 116% and 84 to 103% (n = 3) for flavone A and B, respectively. Stability of both flavones after a freezing/thawing cycle yielded a mean peak ratio ≥0.92 when compared to freshly extracted samples. Intravenous administration of a 20 mg/kg dose in rats yielded half-lives of 83.68 ± 56.61 and 107.45 ± 53.31 min with clearance values of 12.99 ± 13.78 and 80.79 ± 35.06 mL/min/kg for flavones A and B, respectively.